Anti-Inflammatory Secondary Metabolites from Penicillium sp. NX-S-6 - Hanyang Peng; Jiawen Sun; Rui Zhang; Yuxuan Qiu; Yu Hong; Fengjuan Zhou; Chang Wang; Yang Hu; Xiachang Wang (Marine Drugs, 2025)
Five new natural products, including two sorbicillinoids (1–2), one indolinone alkaloid (10), one tetracyclic steroid (11), and one α-pyrone derivative (14), were identified from the endophytic Penicillium sp. NX-S-6, together with thirteen known natural products. The structures of new compounds were unambiguously elucidated by comprehensive spectroscopic analyses (NMR, MS), as well as electronic circular dichroism (ECD) calculation. Notably, quinosorbicillinol (1) was identified as a rare hybrid sorbicillinoid incorporating a quinolone moiety, representing a unique structural scaffold in this natural product class. Biological evaluation revealed that Compounds 1, 4 and 8 potently inhibited the production of nitric oxide and interleukin 6 in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. Mechanistic studies furthermore demonstrated that Compounds 4 and 8 effectively suppressed interleukin-1β secretion in LPS-induced immortalized mouse bone marrow-derived macrophages (iBMDMs) by blocking NLRP3 inflammasome activation. This inhibition was attributed to their ability to disrupt the assembly of the NLRP3-caspase-1 complex, a key event in the pathogenesis of inflammatory disorders. These findings not only expand the structural diversity of endophyte-derived natural products but also highlight their potential as lead compounds for developing anti-inflammatory therapeutics targeting the NLRP3 pathway.